Genetic Diversity, Linkage Disequilibrium, and Genome Evolution in Soft Winter Wheat. Issue 6 (1st November 2014) - Cabrera, Antonio; Souza, Ed; Guttieri, Mary; Sturbaum, Anne; Hoffstetter, Amber; Sneller, Clay
ABSTRACT: Understanding genetic diversity within a breeding population is fundamental to its efficient exploitation. The advent of new high‐throughput marker systems offers the opportunity to expand the scope and depth of our investigation of diversity. Our objective was to analyze the genetic diversity of two populations of soft winter wheat (SW) adapted to the eastern United States. The historical population (HP) consisted of 187 lines released or developed from 1808 to 2005. The elite population (EP) consisted of 449 elite modern lines from the Ohio State University breeding program. The HP was genotyped with single nucleotide polymorphism (SNP) and diversity array technology (DArT) markers, while the EP was genotyped with DArTs. Population structure comprised of up to five subgroups was observed on the HP using either SNP or DArT markers and up to six subgroups on the EP. The subgroups could be partly explained by year of release (in HP), class (red versus white wheat) and pedigree (in the EP). Diversity appeared to increase with time; an estimated 11% of the genome exhibited a pronounced linear change over time, while evidence of more subtle changes abound. The DArT markers were associated with greater genome changes than SNP markers. Linkage disequilibrium (LD) that produced an r 2 of 0.2 or greater extended to about 5 cM in both populations. The extent of LD decay varied widely across the genome. In conclusion, SW in the eastern United States has a moderate level of structure, appears quite diverse, and diversity may be increasing.